Surface microstructures and epoxy bonded shear strength of Ti6Al4V alloy anodized at various temperatures - He, Peigang (2013)
In this paper, the effects of anodizing temperature on the microstructure, composition and surface profile of Ti6Al4V were systematically investigated. Apparent shear strengths of the anodized alloy bonded with epoxy were measured and the fracture mechanisms were analyzed. With increasing anodizing temperatures from 0 °C to 40 °C, the thicknesses of the oxide layer decreased from ∼1200 nm to ∼200 nm, indicating accelerated dissolution process of oxide caused by increased ionic mobility at higher temperature. After anodization at 40 °C, a honeycomb-like oxide layer with pore diameter of 100–200 nm was uniformly developed on Ti6Al4V’s surface. Surface roughness of the oxide layers ranged from 657.0 nm to 817.2 nm. The apparent shear strengths of the specimens anodized at 0 °C, 25 °C and 40 °C were improved by 217.7%, 225.0%, and 317.2%, respectively, in comparison with that of specimen without anodization. From SEM fractomicrographic analysis, pristine specimen showed adhesive failure between epoxy–alloy interface; for specimen anodized at 40 °C cohesive failure of epoxy was dominant; whereas mixed fracture modes, i.e., oxide layer failure, epoxy–alloy interface adhesive failure, and epoxy cohesive failure, were observed for specimens anodized at 0 °C and 25 °C. The nano-engineered honeycomb-like structure contributed to the improved shear strength due to the interlock between anodized Ti alloy and epoxy adhesive, which provides practical solution to tune Ti-based metal-composite interface property for its application to our on-going deepwater composite pipe project.